Lung Abscess and Recurrent Empyema After Infection With Mycoplasma hominis: A Case Report and Review of the Literature. (4th August 2021) - Moneke, Isabelle; Hornuss, Daniel; Serr, Annerose; Kern, Winfried V; Passlick, Bernward; Senbaklavaci, Oemer
Abstract: Mycoplasma hominis is a rarely identified cause of respiratory infection that can cause significant morbidity and mortality in immunocompromised patients. It is often missed due to the difficult detection of the organism with routine laboratory methods. We present the case of a 63-year-old male with a history of lymphoma who was transferred to our hospital with recurrent right-sided empyema and lung abscess in the right lower lobe. Advanced microbiological analysis finally revealed infection with M hominis . Despite appropriate antibiotic treatment, prolonged drainage as well as repeated surgery, which eventually resulted in right lower bilobectomy, were necessary for clinical improvement of our patient. Infection with M hominis may be more prevalent than previously indicated and can cause severe morbidity and mortality in thoracic surgery patients. Due to the diagnostic challenge, the appropriate antimicrobial treatment is often delayed. Inherent resistance to macrolides and inactivity of cell wall-active agents potentially complicate empiric antibiotic therapy. A review of the currently available literature enables a better understanding of the diagnostic difficulties and importance of this infection.